Munasabah antara Ayat-Ayat Al-Qur’an dalam Konsep Ketakwaan - Adawiyah, Rabiatul; Abubakar, Achmad; Ilyas, Hamka; Rif’ah, Muh. Azka Fazaka (Prodi Perpustakaan dan Sains Informasi, 2023)
Munasabah of the Qur'an is a very important principle when trying to understand the Qur'an because we can understand the correlation between verses and the relationship between surahs. The purpose of this research is to understand and understand the correlation of verses in the Koran in faith. The research method used is library research (libray research), namely research by collecting various kinds of data obtained from books which are used as data sources. Understanding munasabah and makes it easier for us to study the Al-Qur'an both in relation to the correlation between one verse and another or the correlation between surahs in the Al-Qur'an. Munasabah Al-Qur'an also plays an important role in obligations in carrying out the teaching and learning process and how to improve teachers' abilities in teaching.